Supercritical CO₂ extraction of jackfruit seeds: article - Che Wang, Che Syahirun Nissa’; Ismail, Norhuda (2019)
Various extraction technique had been used but no research on Supercritical CO₂ extraction (SC- CO₂) of jackfruits seeds has been done. The extraction equipment used in this research is SFT-100 with vital operating variables to be examined were at temperature (50°C, 60°C) with pressure (4000psi, 5000psi, 6000psi). While the extract was tested using Gas Chromatography-Mass Spectrometry (GC-MS), Varian GCMS 450 GC 240 MS Ion Trap. The highest oil yield obtain was 0.31%. There’s 6 major medicinal constituent obtained after analyzed. Jackfruits seeds have the medicinal abilities namely acne treatment, antimicrobial, anticancer, antioxidant, anti-inflammatory and others medicinal values.